Florida Crop/Pest Management Profile: Poultry - Jacqueline Jacob; Olaf Norman Nesheim (EDIS)
This document is CIR 1418, one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Published: February 2003.